Current Therapy of Drugs in Amyotrophic Lateral Sclerosis - Lu, Haiyan; Le, Wei D.; Xie, Ya-Ying; Wang, Xiao-Ping (Current Neuropharmacology, 2016)
Amyotrophic lateral sclerosis (ALS), commonly termed as motor neuron disease (MND) in UK, is a chronically lethal disorder among the neurodegenerative diseases, meanwhile. ALS is basically irreversible and progressive deterioration of upper and lower motor neurons in the motor cortex, brain stem and medulla spinalis. Riluzole, used for the treatment of ALS, was demonstrated to slightly delay the initiation of respiratory dysfunction and extend the median survival of patients by a few months. In this study, the key biochemical defects were discussed, such as: mutant Cu/Zn superoxide dismutase, mitochondrial protectants, and anti-excitotoxic/ anti-oxidative / antiinflammatory/ anti-apoptotic agents, so the related drug candidates that have been studied in ALS models would possibly be further used in ALS patients.
Keywords: riluzole